2009
DOI: 10.1159/000228082
|View full text |Cite
|
Sign up to set email alerts
|

An Inner Medullary Concentrating Process Actuated by Renal Pelvic/Calyceal Muscle Contractions: Assessment and Hypothesis

Abstract: We propose a mechanism of an inner medullary concentrating process in which water extraction is accomplished by a colloid osmotic mechanism and hydrostatic pressure. There are 3 essential features of the proposal: 1. the fluid compartmental structure of the inner medullary interstitium: owing to molecular exclusion, negatively charged macromolecules, i.e. hyaluronan and extravasated plasma albumin form separate compartments (the HA and the EPA compartments); the resulting Gibbs-Donnan effect governs the moveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
2
0
2
Order By: Relevance
“…В почке млекопитающих распределение ГК гетерогенно: высокая концентрация характерна для внутренней зоны мозгового вещества, в то время как в кор ковом веществе содержание ГК в десятки раз ниже (Ivanova et al, 1982;Rügheimer et al, 2008). В высокополимерном состоянии ГК обладает уникальной способностью формировать трехмерный гель, связывать большие объемы воды и положительно заряженные ионы, и это свойство может влиять как на диффузию воды и растворов в медулле почки, так и на поддержание концентрационного градиента (Day, 1952;Hedbys, 1963;Preston et al, 1965;Pinter, Shohet, 2009). Благодаря высокой вязкости ГК также может обладать функцией механо-осмотического преобразователя, конвертирующего энергию перистальтического сокращения гладких мышц почечной лоханки в аксиальный осмотический градиент в сосочке (Knepper et al, 2003;Pinter, Shohet, 2009).…”
Section: How To Cite This Articleunclassified
See 1 more Smart Citation
“…В почке млекопитающих распределение ГК гетерогенно: высокая концентрация характерна для внутренней зоны мозгового вещества, в то время как в кор ковом веществе содержание ГК в десятки раз ниже (Ivanova et al, 1982;Rügheimer et al, 2008). В высокополимерном состоянии ГК обладает уникальной способностью формировать трехмерный гель, связывать большие объемы воды и положительно заряженные ионы, и это свойство может влиять как на диффузию воды и растворов в медулле почки, так и на поддержание концентрационного градиента (Day, 1952;Hedbys, 1963;Preston et al, 1965;Pinter, Shohet, 2009). Благодаря высокой вязкости ГК также может обладать функцией механо-осмотического преобразователя, конвертирующего энергию перистальтического сокращения гладких мышц почечной лоханки в аксиальный осмотический градиент в сосочке (Knepper et al, 2003;Pinter, Shohet, 2009).…”
Section: How To Cite This Articleunclassified
“…Интерес к «гиалуронидазной гипотезе» возобновился в последние годы в связи с появлением новых данных о большой зависимости гиалуронидазной активности и содержания ГК в почке от интенсивности осмотического концентрирования и уровня вазопрессина в крови (Ivanova, Melidi, 2001;Harada, Takahashi, 2007;Rügheimer et al, 2008). Однако вопрос о молекулярных механизмах вовлечения ГК интерстициального матрикса в эффект вазопрессина на транспорт воды в почке остается дискуссионным и требует дальнейших исследований (Pinter, Shohet, 2009;Stridh et al, 2012).…”
Section: How To Cite This Articleunclassified
“…However, thermodynamic analysis of this process indicates that the pressures exerted on the inner medullary tissue can only account for a small fraction of the concentrating work in the inner medulla (70,100). Very recently, Pinter and Shohet (69) suggested that pelvic contractions could contribute to the IM osmolality gradient via a different mechanism, one based on the Gibbs-Donnan effect between two interstitial compartments, one containing hyaluronan and the other extravasated plasma albumin. According to their hypothesis, rhythmic pressure increases could squeeze dilute fluid out of the hyaluronan compartment and simultaneously accelerate the outflow of fluid and albumin into the ascending vasa recta from the extravasated plasma albumin compartment.…”
Section: How Can the Kidney Produce Highly Concentrated Urine?mentioning
confidence: 99%
“…In a highly polymeric state, HA forms a three‐dimensional network, which retains a large volume of water and effects the water and solute flow through the interstitial matrix (Day, 1950, 1952; Hedbys, 1963; Preston et al 1965; Laurent & Fraser, 1992). Owing to the gel‐like conditions and high viscosity, HA may also have the function of a mechano‐osmotic transducer that converts energy from the peristaltic contraction of the pelvic smooth muscle to an axial osmotic gradient in the papilla (Knepper et al 2003; Pinter & Schohet, 2009).…”
Section: Introductionmentioning
confidence: 99%